Ketidaknyamanan pada Perempuan Fluor Albus Fisiologis dengan Intervensi Air Rebusan Sirih Merah - Carolina, Anita; Wahyuni, Sari; Aprilina, Aprilina; Komariah, Nurul; Rohaya, Rohaya; Kamalia, Rita (NHM PRESS, 2025)
Physiological fluor albus, or normal vaginal discharge, is a common phenomenon experienced by women, playing a role in maintaining vaginal cleanliness and moisture. However, limited public understanding often leads to misconceptions and inappropriate management. This study aims to analyze comprehensive midwifery care in a case of physiological fluor albus in Nn. A 16 years old using an intervention of red betel leaf decoction at Puskesmas Tanjung Kerang, Musi Banyuasin, South Sumatera. The study employed a case study method with a descriptive qualitative approach. Data were collected through interviews, SOAP (Subjective, Objective, Assessment, Plan) assessment, observation, and documentation. Interventions included reproductive health education, improved personal hygiene, the use of red betel leaf decoction as a natural antiseptic, recommendations for a nutritious diet, and psychological support. The results indicated that the intervention effectively reduced complaints of vaginal discharge and improved the patient's understanding and healthy habits. The use of red betel leaf decoction proved safe, accessible, and effective in managing physiological fluor albus. This study highlights the importance of local wisdom-based midwifery care approaches in enhancing women's quality of life, especially in rural areas with limited access to healthcare services.